Anti-ulcer potential of Lawsonia inermis l. Leaves against gastric ulcers in rats - Mradul Goswami, Mayank Kulshreshtha, Chandana V. Rao, Sanjay Yadav, Sachdev Yadav (Journal of Applied Pharmaceutical Science)
To evaluate antiulcer effects of aqueous, chloroform and ethanol extracts prepared from the henna leaves in rats employing the pylorus ligation and aspirin induced models. Gastric ulcers induced in Swiss albino rats (200g, N=6) by oral administration of aspirin suspension and pylorus ligation. The antiulcer activity was assessed by determining and comparing the ulcer index in the test drug groups with that of the vehicle control and standard ranitidine. In case of aspirin induced ulcers, the chloroform extract showed significant reduction of ulcers in a dose dependent manner. The parameters taken to assess antiulcer activity were volume of gastric juice, free acidity, total acidity and ulcer index. The results indicated that aqueous, ethanol and chloroform extract significantly (p
Keywords: Lawsonia inermis, Pylorus ligation, Acidity, Ulcer index.